Membangun Komunikasi Yang Baik Antara Orang Tua Dengan Anak Untuk Meningkatkan Prestasi Belajar Anak Kelas III (Studi Kasus di SD Negeri Kenari-Kefamenanu) - Usboko, Wilibrordus Cornelis; Bau, Theabalda D.E. (JURNAL PROPHETA, 2021)
The aim of this study was to determine the role of Catholic religious teachers at Taekas State High School in relation to adolescent self-control, and to measure theeffectiveness of these efforts in improving self-control of Taekas Senior High Schoolstudents. Teachers are people who have knowledge, experience, and are fully responsiblefor the educational process of their students by example and personality so that they candirect students to achieve educational goals. Catholic religious education is faith education that is carried out in a plannedmanner, and strengthens students’ faith in God Almighty in accordance with Catholicreligious teachings, and prepares students to become useful human beings for the Stateand the Church. Adolescent self-control is a process of growth between childhood andadulthood, which is between the ages of 13-17 years in which a person seeks his identityand refuses to act contrary to human norms or to restrain behavior that is painful ordetrimental to others. The method used in this study is a qualitative approach, where theresearcher uses direct interviews with respondents as a tool to collect data. The results of the study found several efforts made by the teacher and the resultsobtained in improving adolescent self-control at Taekas State High School. The effortsinclude: increasing student attendance at school; increasing student activity in theclassroom; most of the students are orderly in school rules and regulations; increasingstudent achievement results; student behavior is in accordance with what is expected sothat unwanted things do not happen.